MARCH8 inhibits influenza A virus infection by targeting viral M2 protein for ubiquitination-dependent degradation in lysosomes - Xiaoman Liu (Nature Portfolio, 2021)
The membrane-associated RING-CH (MARCH) proteins are E3 ligases regulating stability of plasma membrane (PM) proteins. Here, Liu et al. show that MARCH8 suppresses Influenza A virus infection in vitro and in vivo through redirecting M2 protein from the PM to lysosomes for degradation.